Vía PanAm : exploring migration in the Americas = Explorando las migraciones en las Américas - Van Lohuizen, Kadir, 1963-; Corredor, Gerardo; Koopman, Edwin, 1964-; McLean, Anne; Vásquez, Juan Gabriel, 1973- (Edam : Ydoc Pub. : Paradox, 2013)
After the innovative multi-media iPad app and a traveling exhibition, Van Lohuizen's work will now be compiled into a book. This unique publication takes the reader along through the changing landscapes of the countries he travelled. Within these landscapes, the stories of the people pop up, on smaller pages, like intimate little booklets zooming in on the lives of the people that Van Lohuizen portrayed. The photo stories reflect the complexity of migration - the diverse motivations for coming and going, the struggles and successes, the economic, political, social and environmental contexts, as well as the intimate moments and personal stories. Some touching upon current issues, some on topics long forgotten but not resolved. An essay by acclaimed Colombian author Juan Gabriel Vásquez is added. Additional information about migration in the Americas and related issues are presented by way of short texts and info graphics.
Text in English and Spanish.
Keywords: Lohuizen, Kadir van, -- 1963-.; Emigration and immigration -- Pictorial works; Pan American Highway System -- Pictorial works; Photography, Artistic